Aligning Early Childhood Teaching Practices with Parental Aspirations: Insights from a TASKA Case Study. - Aliff Haikal Miftahudin; MOHD NAZRI ABDUL RAHMAN (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
This paper examines the application of teaching and learning strategies among infants and toddlers within Childcare Centres (TASKA) in Malaysia and how the strategies satisfy the wishes of contemporary parents. This paper will utilize teacher interviews and library studies to examine the methods and pedagogical techniques, learning strategies, and challenges faced by the teachers of early childhood learning in the process of delivering holistic and quality care to children under the age of three years. The results indicate that the majority of TASKA focus on the play-based learning, responsive caregiving, and early stimulation activities leading to cognitive, social, and emotional development. Nonetheless, high parental expectations, insufficient resources, and teacher workload continue to be among the difficulties. Some of the recommendations involve the formation of effective teacher-parent collaboration, ongoing professional development, and enhancement of curriculum directives with equal emphasis on academic and development objectives.